Embodied and Symbolic Communication in Islamic Da’wah: Reconstructing ‘Tepuk Sakinah’ as a Strategy for Internalizing Sakinah Family Values - Redi Panuju; Nur’annafi Farni Syam Maella; Ahmad Wahdan Ardi (MASI Mandiri Edukasi, 2026)
The transformation of family structures in contemporary Muslim society has raised concerns regarding the effectiveness of Islamic da’wah in internalizing sakinah family values. Existing studies on da’wah communication have primarily focused on verbal, textual, and digital approaches, while the tangible, symbolic, and participatory dimensions remain underexplored. This study aims to reconstruct Tepuk Sakinah as a manifested and symbolic communication strategy in Islamic da’wah for strengthening the internalization of sakinah family values. A qualitative case study design was employed, with data collected through in-depth interviews, participatory observation, and document analysis at a selected Office of Religious Affairs (KUA). Data were analyzed using an interactive qualitative approach supported by theoretical triangulation. The findings reveal that Tepuk Sakinah functions as a multidimensional communication practice integrating embodied actions, symbolic meanings, and participatory engagement. Through rhythmic movements, collective interaction, and ritual repetition, participants actively construct meaning, develop emotional attachment, and internalize family values more deeply than through cognitive understanding alone. The study contributes to Islamic da’wah and communication scholarship by proposing a symbolic-participatory framework of realized communication and a model for value internalization. Practically, it highlights the significance of experiential and participatory approaches in enhancing the effectiveness of religious communication and strengthening family resilience in contemporary Muslim communities.